Applications of nanofluids in refrigeration and air-conditioning - Sarkar J. (My University, 2025)
Mono and hybrid nanofluids have gained great interest recently in many engineering fields due to their excellent thermophysical, transport, mechanical, and electrical properties, which can be easily used in refrigeration, heat pump, and air-conditioning systems by many roles for performance improvement. This chapter focuses on the applications of mono and hybrid nanofluids in different roles in refrigeration, air-conditioning, and heat pump systems to enhance the performance, such as: (i) nanoparticle-dispersed secondary fluids (as a secondary refrigerant in the evaporator, as a coolant in the condenser, and as a heating fluid in the generator of heat-driven system), (ii) nanoparticle-dispersed refrigerants (called as nanorefrigerants), (iii) nanoparticle-dispersed lubricants (called as nanolubricants), (iv) nanoparticle-dispersed absorbents (called as nanoabsorbents), (v) nanoparticle-dispersed phase-change materials (called as nano-PCMs) in the cold storage system, and (vi) nanoparticle-dispersed fluids in nonconventional systems. Finally, various challenges and future research and development scopes are discussed as well. © 2024 Elsevier Inc. All rights reserved.